The education and training on Augmentative and Alternative Communication for rehabilitation professionals working with people who have little or no functional speech : a scoping review - Samuels, Alecia (University of Pretoria, 2023)
Mini Dissertation (M (Augmentative and Alternative Communication))--University of Pretoria, 2022.